P120 Antenatal blood pressure change across pregnancy in white British and south Asian women by BMI category: analysis using data from the Born in Bradford cohort. (13th September 2016) - Farrar, D; Santorelli, G; Lawlor, DA; Tuffnell, D; Sheldon, TA; Macdonald-Wallis, C
Abstract : Background: The prevalence of hypertensive disorders of pregnancy (HDP) (hypertension and pre-eclampsia) are increasing and are leading causes of maternal and perinatal morbidity and mortality. Increased BMI is a risk factor and evidence suggests that it is also associated with patterns of systolic and diastolic blood pressure (SBP and DBP respectively) change from early pregnancy, but this needs further replication. There is limited evidence of the effects of increased BMI on BP change in different ethnic groups and no evidence from populations in the UK. Our aim was to determine the association of early pregnancy BMI categories with BP change through pregnancy and with HDP in white British (WB) and south Asian (SA) women. Methods: We produced multilevel linear spline models, estimated five parameters ('knot points' at 8, 8–24, 24–30, 30–36, >36 week gestation) and prevalence estimates of HDP for each BMI category in white British and south Asian women using data from the Born in Bradford study. Results: 10, 535 women were included, 4444 were WB and 5427 SA. Patterns of SBP and DBP change over pregnancy by BMI category were broadly similar for WB and SA. SBP and DBP levels were generally higher across pregnancy for WB women compared to SA women for all BMI categories, E.G.: mean SBP (95% CI) for overweight WB and SA at 8 weeks was 111.91 (111.89–111.93) and 107.424 (107.41–107.43) respectively and at > 36 weeks, 117.87 (117.81–117.92) and 112.604 (112.55, 112.66). Underweight WB women start pregnancy with a higher mean SBP, but lower DBP than SA women. The differences between ethnic groups in all categories were generally consistent across pregnancy. For WB and SA women, gestational hypertension and pre-eclampsia prevalence increased across BMI categories. For WB and SA underweight, normal weight, overweight and obese women the prevalence of gestational hypertension was 8.0% (95% CI: 4.2–14.9) and 5.0% (CI: 3.1–8.0), 14.3% (CI: 12.8–16.0) and 9.1% (CI: 8.1–10.2), 23.4% (CI: 21.2–26.0) and 12.0% (CI: 11.0–14.0) and 42.3% (CI: 39.3–45.2) and 25.2% (CI: 22.6–28.0), the prevalence of pre-eclampsia was 4.4% (CI: 1.4–10.7) and 3.4% (CI: 2.9–6.1), 6.5% (CI: 5.4–8.7) and 4.3% (CI: 3.5–5.2), 12.1 (CI: 10.3–14.2 and 6.2 (CI: 5.0–7.2), 27.0 (CI: 24.3–30.1) and 16.0 (CI: 14.0–19.2) respectively. Conclusion: We confirm the association of BMI categories with both gestational hypertension and pre-eclampsia and that prevalences are greater for WB than SA across all categories. We have also shown differences in mean SBP and DBP between WB and SA women and that these differences are consistent throughout pregnancy.